Beneficial and detrimental effects of choline chloride–oxalic acid deep eutectic solvent on biogas production. (15th July 2021) - Lima, Filipa; Branco, Luis C.; Lapa, Nuno; Marrucho, Isabel M.
Graphical abstract: Highlights: ChCl:OA DES toxicity was, for the first time, evaluated in an anaerobic consortium. DES concentration determines a beneficial or negative effect on biogas production. Oxalic acid is the main responsible for the inhibitory effect. The presence of choline chloride improved the production of biogas. Abstract: Deep eutectic solvents (DES), a new class of alternative solvents, have recently been used in the pre-treatment of lignocellulosic biomass. Due to the ability to dissolve phenolic compounds, they have been efficiently applied as delignification agents. However, to extend DES application to bioprocesses, such as Anaerobic Digestion (AD), their toxicity to microbial consortia must be evaluated. In this work, an effective delignifying DES, composed of choline chloride (ChCl) and oxalic acid (OA) (1:1) was prepared and its effect evaluated, for the first time, in biogas production. Results show that the presence of DES had both beneficial and detrimental effects on the anaerobic consortium, depending on its concentration. In the concentration range of 0.3–12.5 g/L, the presence of DES led to a lag-phase of 1 to 8 d as the DES concentration increased. However, after the lag-phase has been surpassed, DES up to a concentration of 12.5 g/L improved the biogas production, reaching an accumulated biogas volume three times higher than the control assay for the concentration of 12.5 g/L. For the highest DES concentrations (19.8–78.1 g/L), the biogas production was inhibited. The assays performed with DES components alone have indicated that OA at 3.2 g/L was the main responsible for the inhibition of biogas production (50% less biogas produced than the control). ChCl at 4.9 g/L has not presented a lag-phase and produced an accumulated biogas volume like the control assay (1200 mL for 30 d incubation). This work points out that ChCl:OA DES may be used in the delignification of biomass further submitted to AD, provided the inhibitory concentrations of OA are not achieved.